Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ani13203213
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Reserves, Non-Esterified Fatty Acids, and Leptin during the Reproductive Lifespan of the Rabbit Female

Rosa Peiró,
María-José Argente,
María-Luz García

Abstract: The aim of this work is to study changes in body weight, perirenal fat thickness (PFT), and non-esterified fatty acid (NEFA) and leptin concentrations throughout the reproductive life of the rabbit female and their correlations when a semi-intensive reproductive rhythm is applied. A total of 46 lactating females were used. Body weight, PFT, and NEFA and leptin concentration were recorded at 12 weeks of age, at first mating and delivery, and at second, third, and fourth mating, 12th d of gestation, and delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…NEFA undergo metabolism through beta-oxidation at the mitochondrial level to generate energy. The NEFA levels, averaging 575 µ eqv./L in this study, align closely with values reported for productive rabbits 28 , 29 , and are lower than those noted in the same wild species 30 – 32 . In this work, we have obtained 36% more of this metabolite in animals fed on Diet U.…”
Section: Methodssupporting
confidence: 89%
“…NEFA undergo metabolism through beta-oxidation at the mitochondrial level to generate energy. The NEFA levels, averaging 575 µ eqv./L in this study, align closely with values reported for productive rabbits 28 , 29 , and are lower than those noted in the same wild species 30 – 32 . In this work, we have obtained 36% more of this metabolite in animals fed on Diet U.…”
Section: Methodssupporting
confidence: 89%